The Sex Difference in Rod Balancing: Confirmation of the Difference and a Test of Three Hypothetical Explanations. Issue 3 (December 2015) - Porras, Ileana C.; Hiscock, Merrill; Layne, Charles S.
Previous studies have shown that men can balance a dowel rod on the index finger for a longer time than women can. The factors that account for the difference are unknown, but the difference may be attributable either to a difference in whole-body agility or a difference in the use of visual cues. Three experiments involving a total of 62 adult women with a mean age of 21.2yr. ( SD = 3.8) and 62 adult men with a mean age of 21.9yr. ( SD = 6.6) tested these potential explanations. Experiment 1 replicated the sex difference and assessed the relevance of whole-body agility by comparing standing and seated conditions. Experiments 2 and 3 explored the role of rod length and visual fixation point, respectively. Each experiment yielded a significant sex difference, but the difference was not affected by the participant's posture, the length of the rod, or the fixation point. Possible alternative explanations for the difference include differences in (1) the speed of processing degree of visual tilt; (2) arm mass, which affects the inertia of the balancing system; and (3) experience in open-skill sports.